Do the following operations:

- $$(-6)+3\cdot(-2)=$$
- $$(4+7)\cdot 2^2=$$
- $$(18+(-3)):5-(-2)=$$

See development and solution

### Development:

1)

- There is no operation in brackets, therefore we pass to the next step.
- There is no power, therefore we pass to the next step.
- There is only a multiplication and there is no division. It is: $$3\cdot(-2)=-6$$. So far, the expression is: $$(-6)+(-6)$$
- There is only one addition and there is no subtraction: $$(-6)+(-6)=-12$$ Therefore: $$(-6)+3\cdot(-2)=-12$$.

2)

- There is an operation in brackets: $$(4+7)=11$$ Therefore, we have: $$11 \cdot 2^2$$
- There is a power: $$2^2=4$$. And so, we have: $$11\cdot4$$
- We do the multiplication, the result: $$11\cdot4=44$$ So: $$(4+7)\cdot 2^2=44$$

3)

- There is an operation in brackets: $$(18+(-3))=15$$ Therefore, it is: $$15:5-(-2)$$
- There is no power. Therefore, we pass to the next step.
- There is no multiplication, but there is a division. And it is: $$15:5=3$$ The expression is: $$3-(-2)$$
- There is only a subtraction: $$3-(-2)=5$$ Therefore: $$(18+(-3)):5-(-2)=5$$

### Solution:

- $$(-6)+3\cdot(-2)=-12$$
- $$(4+7)\cdot 2^2=44$$
- $$(18+(-3)):5-(-2)=5$$